Advantages of vertical axis tidal turbines set in close proximity: A comparative CFD investigation in the English Channel. (15th May 2018) - Zanforlin, Stefania
Abstract: A 2D CFD analysis of the hydrodynamic interactions between three closely spaced Vertical Axis Tidal Turbines is performed for two layouts: side-by-side and triangular. Three mechanisms determine a power increase with respect to isolated turbines: (1) turbine blockage that entails flow acceleration outside of the turbines and inside the aisles between adjacent turbines; (2) more favorable direction of the flow approaching the blade during upwind trajectory; (3) wake contraction, that increases the torque generation during the downwind path. Blockage is responsible for a moderate performance increase exhibited by the triangular layout. Change in direction of the flow approaching the blades and wake contraction only occur for the side-by-side layout and cause a significant increase in efficiency. The six-month energy production of the two arrangements is predicted for three real cases in the English Channel: Alderney Race, St. Catherine and Portland Bill, characterized by rectilinear and non-rectilinear currents. Passive stall is assumed as load strategy control; the effect of the rated speed on energy production is analyzed. The side-by-side layout allows not only a higher power gain but also a wider range of flow directions for which a gain is possible, therefore it appears suitable even for non-rectilinear currents. Highlights: Favorable layouts cause high attack angle in upwind, wake contraction in downwind. Azimuthal distribution of flow attack angle and x-velocity can explain power gains. Side-by-side layouts entail energy gains even up 20% for rectilinear currents. Side-by-side layouts entail energy gains even up 10% for non-rectilinear currents. Blockage effects are not satisfactorily exploitable with passive stall load control.